Enhancing stock investment: why knowing investor types matters? / Syukriah Ali, Najah Mokhtar and Rosliza Md Zani - Ali, Syukriah; Mokhtar, Najah; Md Zani, Rosliza (Universiti Teknologi MARA, Kedah, 2023)
Investment can be defined as the commitment of funds to one or more assets that will be held over some future period (Jones, 2010). Investing can refer to various activities for instance, putting money into shares, certificates of deposit, bonds or mutual funds. It includes both very conservative positions and aggressive speculation. In the world of investing, navigating the financial markets can be a complex and challenging endeavor. The dynamic nature of markets and influenced by a multitude of factors demands the players involved to have a deep understanding of investment. Traders play their important role in shaping market dynamics, driving price movements, and influencing investment outcomes. Recognizing the importance of comprehending the different types of traders is crucial for investors seeking to make informed decisions and achieve their financial goals. The lack of awareness and understanding regarding the different types of traders poses a significant challenge for investors entering the financial markets. Without sufficient knowledge of trader behaviors, strategies, and their impact on market dynamics, investors may struggle to make informed investment decisions, manage risks effectively, or capitalize on potential opportunities. Therefore, there is a pressing need to emphasize the importance of knowing the types of traders to equip investors with the essential insights required for successful navigation of the complex investment landscape. Traders are broadly classified into four types namely the scalper, the day trader, the swing trader, and the position trader, and these four certainly have different trading skills requirements. By exploring the characteristics, strategies, and behaviors of different trader types, investors can gain valuable insights that enhance their ability to navigate the markets effectively. This knowledge empowers them to make more informed decisions, manage risks prudently, and seize potential opportunities with greater confidence.